2016
DOI: 10.1186/s13048-016-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Successful live birth in a woman with resistant ovary syndrome following in vitro maturation of oocytes

Abstract: BackgroundResistant ovary syndrome (ROS) is a rare endocrine disorder characterized with hypergonadotrophic hypogonadism. Infertility is a common complaint of woman presenting with ROS, and little progress has been made in term of reproduction with the patient’s own gamete. So far only one case report of live birth has been reported after in vitro maturation (IVM) of oocytes in a patient suffering from ROS in 2013.Case presentationA secondary infertile woman of 33 years-old was manifested with oligomenorrhea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
2
23
1
Order By: Relevance
“…Gonadotropin-resistant ovary syndrome (gonadotropin-ROS) or ROS, first described by Jones and De Moraes-Ruehsen [14] in 1969, is known to be one of the causes of ovarian failure leading to primary or secondary amenorrhea. The presence of a normal amount of antral follicles is a criterion that distinguishes ROS from the classical POI [14,15]. Besides an age-compatible number of small antral follicles, additional cardinal clinical features of ROS are normal chromosome, elevated gonadotropin levels of menopausal range, and unresponsiveness to gonadotropin stimulation [15], all of which are consistent with our cases.…”
Section: Discussionsupporting
confidence: 89%
“…Gonadotropin-resistant ovary syndrome (gonadotropin-ROS) or ROS, first described by Jones and De Moraes-Ruehsen [14] in 1969, is known to be one of the causes of ovarian failure leading to primary or secondary amenorrhea. The presence of a normal amount of antral follicles is a criterion that distinguishes ROS from the classical POI [14,15]. Besides an age-compatible number of small antral follicles, additional cardinal clinical features of ROS are normal chromosome, elevated gonadotropin levels of menopausal range, and unresponsiveness to gonadotropin stimulation [15], all of which are consistent with our cases.…”
Section: Discussionsupporting
confidence: 89%
“…In 5-10% of cases of POI, however, pregnancy can occur naturally, with hormone replacement therapy (HRT), IVF, or, more recently, in-vitro maturation (IVM) or with stem cell therapy . Numerous case reports also support this statement (TABLE 1) (Check et al, 2000;Nawroth et al, 2000;Zargar et al, 2000;Takahashi et al, 2001;Fernandes, 2002;Hershlag and Schuster 2002;Chao et al, 2003;Eldeen and Fawzi, 2003;Muller et al, 2003;Patel et al, 2003;Aslam et al, 2004;Menezo et al, 2004;Vital-Reyes et al, 2004;Corrigan et al, 2005;Check and Katsoff, 2006;Vandborg and Lauszus, 2006;Liza et al, 2008;Dragojevic-Dikic et al, 2009;Genazzani, 2009;Neves-e-Castro, 2009;Selvaraj et al, 2010;Chen and Chen, 2011;Ebrahimi et al, 2011, Ferrau et al, 2011Laway et al, 2011;Tartagni et al, 2011;Ghazeeri and Awwad, 2012;Grynberg et al, 2013;Maruyama et al, 2013;Soave et al, 2013;Tsuji et al, 2013;Rogenhofer et al, 2014;Warenik-Szymankiewicz and Slopien 2014;Roth and Alvero, 2014;Li et al, 2016).…”
mentioning
confidence: 89%
“…Papers on IVM before 2009 showed low implantation and pregnancy rates but after the publication of Pak et al ( 32 ) , the results were comparable with IVF. PCOS and OHSS are the main indications of IVM; however, IVM may also be used in cases of resistant ovary syndrome and fertility preservation as uncommon indications ( 33 , 34 , 35 ) . Child et al ( 36 ) studied the impact of IVM on PCO, PCOS, and unstimulated normal ovaries and concluded that hCG priming in all three groups had similar high maturation, fertilization, and developmental potential.…”
Section: Discussionmentioning
confidence: 99%